2016
DOI: 10.7860/jcdr/2016/20486.7939
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Bacterial Colonization and Biofilm Formation Property of Uropathogens between the Two most Commonly used Indwelling Urinary Catheters

Abstract: The pure silicone catheter is advantageous over the silicone coated latex catheter in terms of incidence of bacterial colonization as well as the biofilm formation and hence in the management of CAUTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…Due to frequent and sometimes unnecessary use of catheters, CA-UTIs, equate for 8-35% of healthcare-related infections [5,6], and are the second most common cause of septicaemia which is associated with substantially increased mortality [7][8][9]. Studies have shown that between 15-25% of the patients admitted in hospital require urinary catheterisation [10] which increases their risk of developing urinary tract infection by 5% per day [11,12]. In 30 -40% of the patients suffering from CA-UTI microorganisms may enter blood and progress to septicaemia, which accounts for 8% of all nosocomial infections [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to frequent and sometimes unnecessary use of catheters, CA-UTIs, equate for 8-35% of healthcare-related infections [5,6], and are the second most common cause of septicaemia which is associated with substantially increased mortality [7][8][9]. Studies have shown that between 15-25% of the patients admitted in hospital require urinary catheterisation [10] which increases their risk of developing urinary tract infection by 5% per day [11,12]. In 30 -40% of the patients suffering from CA-UTI microorganisms may enter blood and progress to septicaemia, which accounts for 8% of all nosocomial infections [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that between 15-25% of the patients admitted in hospital require urinary catheterisation [10] which increases their risk of developing urinary tract infection by 5% per day [11,12]. In 30 -40% of the patients suffering from CA-UTI microorganisms may enter blood and progress to septicaemia, which accounts for 8% of all nosocomial infections [10]. 1 in 3 patients who acquire bacteraemia in blood will eventually die of the infection [13].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, inhibiting biofilm formation in drug-resistant K. pneumoniae may reduce their resistance to host-mediated defenses 29 and weaken their colonizing ability, thereby increasing their susceptibility to antimicrobial agents. 30 Nevertheless, there are some limitations of this study. First, the sample size was limited.…”
Section: Discussionmentioning
confidence: 89%
“…(16) As an alternative to reduce urethral infl ammation, the use of silicone Foley catheter was effi cient, but it was not able to minimize biofi lm formation. (17) By contrast, other authors reported a decrease in risks of inlaying and biofi lm formation in silicone Foley catheters when compared to those made of latex, depending on the type of microorganism. (2,18) Th us, biofi lms can be formed by a single type of bacteria or several species, with the possibility of forming structures that are three-dimensional, heterogeneous and highly resistant to physical and chemical agents.…”
Section: Discussionmentioning
confidence: 94%